INDUSTRIALIZATION ANALYSIS IN SURODADI VILLAGE COMMUNITY - Nanik Hidayati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
A decent and well-established economy is an indicator of community welfare. Economic improvement and development are supported by industrial progress in an area. The existence of the industry will have an impact on the area as happened in Surodadi Village which experienced development after the construction of PT. CJ CheilJedang Feed Semarang is the largest company in Surodadi Village by producing animal feed and fish feed with its head office in South Korea. This research is a qualitative descriptive study that describes the impact of PT. CJ CheilJedang Feed Semarang on the living conditions of the Surodadi Village community. The object of research is PT. CJ CheilJedang Feed Semarang and Surodadi Village, while the research subjects were the Surodadi village community, employees, local government, and related agencies. Data comes from primary data in the form of primary sources directly obtained from research results, as well as secondary data from literature and document studies. The data was obtained from the results of observations, interviews, and field documentation. Data analysis with stages of data collection, data reduction, data presentation, and conclusions. The analysis of the validity of the data with data triangulation techniques and sources. The results showed the existence of PT. CJ CheilJedang Feed Semarang creates job opportunities (reduces unemployment), develops community business units (food stalls, shops, boarding houses, rented houses), improves community welfare. The negative impact is in the form of odor pollution which sometimes reaches residents' settlements as well as heavy traffic during the hours of leaving and returning from work.